Statement by the Managing Director to the International Monetary and Financial Committee on the IMF Reform Agenda. (Policy Papers; Policy Paper, 2010)
The recent financial crisis has given renewed urgency to the need for resolution systems for financial institutions, which both safeguard financial stability and limit moral hazard. However, experience demonstrates that these systems will not be effective unless progress is also made in developing a framework that applies on a cross-border basis. Since many systemically important financial groups operate globally, an uncoordinated application of resolution systems by national authorities will make it much more difficult to both secure the continuity of essential functions (thereby limiting contagion), and ensure that shareholders and creditors bear the financial burden of the resolution process.